ANALYSIS OF THE EFFECT OF INDONESIAN DEFENSE BUDGET POLICY ON NATIONAL ECONOMIC GROWTH - Posma Sariguna Johnson Kennedy (Association of Certified Fraud Examiners Indonesia Chapter, 2017)
ABSTRACTThis study aims to show that budget policy is not only to strengthen defense equipment to the “minimum essential force”, but it should not be forgotten that budget policy also provide a multiplier effect on economic growth. The use of a good defense budget can be seen from the extent to which the budget affects the economic growth. This influence is tested by using a single equation of economic growth that is built from the supply side. Regression results of the quartile data of 1991-2010 show that the increase in the national defense budget turns out to have no effect on economic growth and gives negative externalities to the private sector. But, non-defense government budgets provide positive externalities to the private sector. This indicates that the non-defense budgets are able to provide a multiplier effect on the economy, but the defense budget has no effect on the economic sectors directly. So, the defense budget policies must give effect to the national economy, such as increased production with the development of the defense industry to meet the domestic needs of defense equipment.